How Innocent Is Corpus Callosum Dysgenesis? - Erol, Fatih Serhat; Ozturk, Sait; Akgun, Bekir; Cakin, Hakan; Kaplan, Metin (Karger, 2013)
Background/Aims: We aimed to investigate the relationship between corpus callosum dysgenesis (CCD) and associated asymptomatic closed spinal dysraphisms (CSDs). Methods: 2,840 pediatric patients who were referred to our outpatient clinic between the years 2005 and 2013 with the diagnosis of microcephaly, macrocephaly, congenital hydrocephaly, epilepsy, mental-motor retardation and suspicion of intracranial mass were evaluated. Eighty-five patients were identified with a CCD by cranial magnetic resonance imaging (MRI). The 85 patients with CCD were evaluated by whole spinal vertebral MRI for possible CSD and the results were evaluated. Results: 31/85 (36.4%) patients (20 males, 11 females) were detected to have radiological findings of CSD. The most common radiological finding was a low-lying conus medullaris, either alone, or as part of a multiple pathology in 26 of the 31 patients, followed by diastematomyelia in 16 of 31 cases and spinal lipoma in 4 of the 31 cases. Conclusion: When the neuroaxis emerges as a whole, the structures of embryological ectodermal origin and cranial and spinal structures are not independent regions from each other and thus, asymptomatic CSDs have been demonstrated to accompany CCD. In diseases of neural origin in which early diagnosis is of the utmost importance, each case with dysgenesis, diagnosed incidentally or during differential diagnosis, should be evaluated for possible CSD and should be treated with a multidisciplinary approach before any neurological deficit appears. (C) 2013 S. Karger AG, Basel
Keywords: Corpus callosum dysgenesis; Diastematomyelia; Low-lying conus; Spina bifida occulta; Tethered cord syndrome